The fast radio burst dispersion measure distribution. Issue 4 (30th December 2020) - Arcus, W R; Macquart, J-P; Sammons, M W; James, C W; Ekers, R D
ABSTRACT: We compare the dispersion measure (DM) statistics of FRBs detected by the ASKAP and Parkes radio telescopes. We jointly model their DM distributions, exploiting the fact that the telescopes have different survey fluence limits but likely sample the same underlying population. After accounting for the effects of instrumental temporal and spectral resolution of each sample, we find that a fit between the modelled and observed DM distribution, using identical population parameters, provides a good fit to both distributions. Assuming a one-to-one mapping between DM and redshift for an homogeneous intergalactic medium (IGM), we determine the best-fitting parameters of the population spectral index, α , and the power-law index of the burst energy distribution, γ , for different redshift evolutionary models. Whilst the overall best-fitting model yields α =2.2_-1.0^+0.7 and γ =2.0_-0.1^+0.3, for a strong redshift evolutionary model, when we admit the further constraint of α = 1.5 we favour the best fit γ =1.5 ± 0.2 and the case of no redshift evolution. Moreover, we find no evidence that the FRB population evolves faster than linearly with respect to the star formation rate over the DM (redshift) range for the sampled population.